35th AIAA Fluid Dynamics Conference and Exhibit 2005
DOI: 10.2514/6.2005-5267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Control of Transonic Cavity Flow Using DES and LES

Abstract: Numerical simulations of the flow inside a cavity with a length-to-depth ratio (L/D) of 5 and a width-to-depth ratio (W/D) of 1 have been conducted using Large-Eddy Simulation (LES) and Detached-Eddy Simulation (DES). The cavity is exposed to a free-stream of zero incidence, M ∞ = 0.85 and Re = 1 × 10 6 (based on the cavity length). Previous numerical simulations of 3D cavities using Unsteady Reynolds-Averaged Navier-Stokes (URANS) have proved difficult in accurately predicting the noise level and frequency co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…It was found that this method provides higher accuracy than DES method 9 for the grid with the same number of cells. Its accuracy is comparable with the results that were obtained using LES method, 9 whose number of cells was twice as many. In this paper the influence of SJs on the flow in the three-dimensional cavity of M219 was studied using RANS/ILES method.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…It was found that this method provides higher accuracy than DES method 9 for the grid with the same number of cells. Its accuracy is comparable with the results that were obtained using LES method, 9 whose number of cells was twice as many. In this paper the influence of SJs on the flow in the three-dimensional cavity of M219 was studied using RANS/ILES method.…”
Section: Introductionsupporting
confidence: 83%
“…Narrowband spectra are shown for cases, which have the greatest impact on the level of the peak values on the back wall of the cavity (see Figure 6). Analysis showed that spectra in the pairs of point (1,4), (2,5), (3,6) (7,9), and (8,10) are rather close, so results for most cases will be presented only for the points which are located in the section z ¼ 0. For M 0 ¼ 0.85 four jets before the cavity (case no.…”
Section: Results Of Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparing the 2-D and 3-D resonance cases, it was consistently observed that 3-D excitation generated less broadband amplification than 2-D. This supports the attribution of the broadband reduction to the 3-D nature of excitation by the subsonic work [25,34]. Figure 13 shows 2-D and 3-D excitation spectral differences.…”
Section: Discussion Of Strongly Resonating Resultssupporting
confidence: 52%
“…The peak tone at the second Rossiter mode has decreased by almost 8 dB, and the average broadband spectra has decreased by roughly 3 dB. Because the forcing is not truly two-dimensional, it is believed that the broadband reduction is at least partially due to modest three-dimensionality imposed on the nominally two-dimensional cavity flow [41]. The presence of EMI makes the interpretation of the results more difficult, but it appears that forcing at this frequency induces some jitter in the second Rossiter mode, making it broader, and promotes amplification (though not significantly) of other modes.…”
Section: B Strongly Resonating Flow 1 Quasi-two-dimensional Controlmentioning
confidence: 99%